2018
DOI: 10.1038/s41598-018-21564-x
|View full text |Cite|
|
Sign up to set email alerts
|

Removal of artificial sweeteners and their effects on microbial communities in sequencing batch reactors

Abstract: Concern is growing over contamination of the environment with artificial sweeteners (ASWs) because of their widespread existence in wastewater treatment plants (WWTPs). To evaluate ASWs removal and the effect on activated sludge, acesulfame (ACE), sucralose (SUC), cyclamate (CYC) and saccharin (SAC) were introduced individually or in mixture to sequencing batch reactors (SBRs) in environmentally relevant concentrations (100 ppb) for 100 days. Comparisons between ACE removal in a full-scale WWTP and in lab-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 52 publications
1
3
0
1
Order By: Relevance
“…In this study, the dose of artificial sweeteners (0.3-3 mg/L) is environmentrelated range (2.5 mg/L in WWTPs [70]). The concentrations of artificial sweeteners in the environment would be higher because of persistence, accumulation and the growing consumption of artificial sweeteners [71][72][73]. Moreover, extracellular DNA molecules are very abundant (over 100 µg/g dry sludge [74] or up to 30 ng/µL [75], which is far higher than 0.8 ng/µL used in the present study) and can be persistent over 20 weeks [76] in the environment.…”
Section: Implications To Public Health and Environmental Risk Managementmentioning
confidence: 63%
“…In this study, the dose of artificial sweeteners (0.3-3 mg/L) is environmentrelated range (2.5 mg/L in WWTPs [70]). The concentrations of artificial sweeteners in the environment would be higher because of persistence, accumulation and the growing consumption of artificial sweeteners [71][72][73]. Moreover, extracellular DNA molecules are very abundant (over 100 µg/g dry sludge [74] or up to 30 ng/µL [75], which is far higher than 0.8 ng/µL used in the present study) and can be persistent over 20 weeks [76] in the environment.…”
Section: Implications To Public Health and Environmental Risk Managementmentioning
confidence: 63%
“…In the environmental setting, although various techniques, including adsorption, advanced oxidation processes, and biological treatment, are used to remove nonnutritive sweeteners, the removal efficiency of these sweeteners is generally low (less than 30%) [41][42][43]. We also found that nonnutritive sweeteners used were metabolically resistant to the tested bacterial strains (p = 0.062~0.700; see in Text S4; Fig.…”
Section: Discussionmentioning
confidence: 76%
“…The completed degradation of paracetamol in the CAS system was previously reported 168 . Similarly the complete removal of caffeine, paraxanthine, cyclamate, saccharin, cotinine and OH-cotinine were largely comparable to the previously reported removal (%) in the CAS treatment process 118,124,146 (appendix B, Table B2).…”
Section: Fate Of Mps In the Steady-state Sbr Reactorsupporting
confidence: 86%